Vivências e expressões da nova paternidade no cenário de uma maternidade pública do nordeste brasileiro. - Batista, Laudeci Brito (2017)
From the second half of the twentieth century Brazilian society presented socio-cultural, economic and family changes which marked the construction of masculinity and parental care and which culminated in the advent of the new paternity, proposing a masculine attention that gives to man a bigger parental presence in domestic space and implies new meaning in the affective dimension of the father in relation to the child. However, this transformation is not exempted of tensions and it includes to the man traditional attributes added to new convictions. In this sense, the new paternity occurs from the inclusion and amplification of the involvement of the man-father in the context of the labor and childbirth and acquires a new meaning. The objective of this study is to comprehend the meanings that man attributes to his perception in the performance of paternity in the context of labor and childbirth in a public maternity hospital of Brazilian Northeast. This is a study with a qualitative approach that used the triangulation of methods: ethnography and in-depth interview done at the Instituto de Saúde Elpídio de Almeida - ISEA in the city of Campina Grande - PB. The data were collected during the months of April to May 2016, which population was determined by intentionality, with the interviews recorded in digital devices and later transcribed in totality, and the number of interviews defined by the criterion of theoretical saturation. As for the analysis of the empirical data, from the study of content, three analytical categories were constructed: 1- Expressions of paternity; 2. Meaning of being a father; 3 - how it is for this man being in the process of labor and childbirth. This study evidenced as main results the differences and similarities in the ways of being a father and of taking care, depending on the sector unit and the stages of laboring experienced, highlighting the support and shelter focused on women, suggesting a perspective of care attribution mediated by the mother considering the corporality of the fetus and the conjugal relationship. Although the man-father expresses availability for the care and the follow-up of the woman in labor, he did in an inconsistently form and putting himself as a support. As for the meaning of being a father, there were parents who as soon as they perceived themselves still in gestation, others from the childbirth and some related to the value and quality of their conjugal relationship. Being present in the labor and childbirth scenario offered openness to the living of paternity assuring the man to live an unique moment in life through the birth of the child and, on the other hand, made a problem of his presence, since there are still barriers of man himself, professionally and institutionally which separate the father from the birth scene, interfering with the father and child relationship. Thereby, the new paternity in the maternity scenario permits the expressions of the different modalities of being a father and that is why it becomes a relevant theme for the field of collective health.